2011
DOI: 10.4040/jkan.2011.41.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity and Reliability of the Korean Version of the Practice Environment Scale of Nursing Work Index for Korean Nurses

Abstract: Purpose: To develop and test the validity and reliability of the Korean version of PES-NWI measuring nursing work environments in hospitals. Methods: The Korean version of the PES-NWI was developed through forward-backward translation techniques, and revision based on feedback from focus groups. An internal consistency reliability and construct validity using confirmatory factor analysis were conducted using SPSS WIN (16.0) and AMOS (18.0). Survey data were collected from 733 nurses who worked in three acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
90
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(111 citation statements)
references
References 15 publications
13
90
2
6
Order By: Relevance
“…Overall, participants were neutral or undecided about their work environment. The results were similar to those of previous studies conducted with nurses at high‐class general hospitals located in Korea (Cho et al, ; Kim & Yom, ). The American Nurses' Credentialing Center grants a certification called Magnet hospital to institutions that have good working environments to encourage the provision and maintenance of high‐level nursing services (Lake & Friese, ).…”
Section: Discussionsupporting
confidence: 91%
“…Overall, participants were neutral or undecided about their work environment. The results were similar to those of previous studies conducted with nurses at high‐class general hospitals located in Korea (Cho et al, ; Kim & Yom, ). The American Nurses' Credentialing Center grants a certification called Magnet hospital to institutions that have good working environments to encourage the provision and maintenance of high‐level nursing services (Lake & Friese, ).…”
Section: Discussionsupporting
confidence: 91%
“…Nursing work environment had the second greatest impact on nurses’ intent to leave, which was also consistent with previous results (Currie & Carr Hill, ; Lu et al, ; Moon & Han, ). As nursing work environment can also enhance the quality of various services provided by nurses (Lake, ), improving an organisation's productivity and boosting the social perception of nurses (Cho et al, ), it is crucial to develop specific and diverse measures to improve nursing work environment. Burnout was also found to affect nurses’ intent to leave, corroborating previous studies (Kang & Kim, ; Lu et al, ; Nantsupawat et al, ) that have reported burnout hinders nurses’ work performance by inducing psychological pressure and physical problems in nurses (Lake & Friese, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurse staffing was computed as the average number of patients that nurses reported caring for on their last shift. The nurse work environments were measured using the Korean Practice Environment Scale of the Nursing Work Index (PES-NWI) (Cho et al, 2011), which is composed of 29 items scored using a Likert-type scale (from 1 = strongly disagree to 4 = strongly agree) that are summed to form five subscales (nurse participation in hospital affairs, nursing foundation for quality of care, nurse manager ability-leadership-support of nurses, staffing–resource adequacy, and collegial nurse–physician relationship). The average of each subscale for all nurses in each hospital was calculated, as was the overall medians for each subscale across all hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Hospitals with four or five of the subscale totals above the median were categorized as having “better” work environments, those with two or three subscale totals above the median were categorized as providing “mixed” work environments, and those with only one or no subscale total above the median were categorized as having “poor” work environments. The reported Cronbach’s alpha of these five subscales in the original PES-NWI ranged from 0.71 to 0.84 (Lake, 2002), and the Cronbach’s alpha for these subscales in the Korean PES-NWI ranged from 0.80 to 0.84 (Cho et al, 2011). Nurse education was measured by calculating the percentage of nurse respondents in each hospital with at least a Bachelors’ degree.…”
Section: Methodsmentioning
confidence: 99%